Surgical treatment of heart failure due to giant coronary artery fistula: a case report. (23rd July 2020) - Sandor, Barbara; Bogats, Gabor; Toth, Levente; Habon, Tamas
Abstract: Coronary artery fistula is a rare congenital cardiac anomaly that is often found incidentally during computed tomography angiography. Coronary fistula between the left circumflex coronary artery and the coronary sinus is among the less common forms of coronary artery fistula. A 60‐yea\r‐old female patient presented to our outpatient cardiology department with symptoms of severe, de novo heart failure. Echocardiogram revealed severe mitral regurgitation and a dilated duct that turbulently accelerated colour Doppler flow behind the left ventricle with significant left‐to‐right shunt. Cardiac magnetic resonance imaging and computed tomography angiography revealed a massively dilated fistula between the left circumflex coronary artery and the coronary sinus with a diameter of 3–4 cm. The patient underwent combined heart surgery involving mitral ring annuloplasty and fistula ligation and was discharged in stable condition on guideline‐based medical therapy. At 18 months of follow‐up, minimal residual shunt flow and mild‐to‐moderate mitral regurgitation were found. We report a rare case of congenital coronary disorder resulting in heart failure and highlight the importance of complex non‐invasive cardiac diagnostic procedures before planning and performing heart surgery.